Enhancing gougerotin production by screening endogenous promoters for the transporter gene gouM in Streptomyces albulus CK-15 - Liu, Binghua; Zhou, Qianying; Qiao, Ruixin; Zhou, Kunping; Zhang, Ning; Ge, Beibei (Frontiers in Microbiology, 2026)
IntroductionGougerotin is a nucleoside antibiotic that exhibits strong inhibitory effects against bacteria, as well as activities against plant viruses and pathogenic fungi, making it highly valuable for development and application. However, its widespread use is limited by low production yield and long fermentation time. In the gougerotin biosynthetic gene cluster, the gouM gene is a transporter gene, and its encoded protein is responsible for transporting gougerotin to the extracellular space.MethodsTo validate the impact of the gouM gene on gougerotin production, we generated a mutant strain by knocking out the gouM gene. To enhance the expression level of the gouM gene and thereby improve its ability to transport gougerotin, we screened endogenous promoters to drive the expression of the gouM gene through experiments including transcriptome sequencing, analysis, and measurement of mCherry fluorescence intensity.ResultsThe mutant strain S. albulus ΔgouM produced 508.34 mg/L of gougerotin, a 58.01% reduction compared to the wild-type strain (1212.74 mg/L). The results indicate that the transporter gene gouM significantly affects the yield of gougerotin.We screened seven suitable endogenous promoters (PT1, PT2, PT3, PM3, PM4, PL2, and PL3). Each of these promoters was then used to drive the expression of the gouM gene. Among them, the gougerotin yields of strains with gouM driven by PT1 and PT2 promoters were 1451.11 mg/L and 1474.58 mg/L, which represented increases of 19.65% and 21.59%, respectively, compared to the wild-type strain.DiscussionThis study demonstrates that using strong promoters to enhance the expression level of the transporter gene gouM can increase the yield of gougerotin, thereby providing a basis for subsequently using promoter engineering strategies to construct higher-yielding strains in the future.